Memorializing William Tyndale. Issue 1 (1st April 2014) - Atherstone, Andrew
Abstract: William Tyndale, the Bible translator and Reformation martyr, enjoyed a sudden revival of interest in the mid-nineteenth century. This article examines one important aspect of his Victorian rehabilitation - his memorialization in stone and bronze. It analyses the campaigns to erect two monuments in his honour - a tower on Nibley Knoll in Gloucestershire, inaugurated in 1866; and a statue in central London, on the Thames Embankment, unveiled in 1884. Both enjoyed wide support across the political and ecclesiastical spectrum of Protestantism, and anti-Catholicism was especially prominent in the first initiative. Both monuments emphasized the blessings of the Bible in English, the importance of religious liberty, and the prosperity of England and the Empire as a result of its Reformation heritage. The article argues that controversy concerning Tractarianism and biblical criticism was brushed under the carpet, and Tyndale's distinctive evangelical theology was deliberately downplayed, in order to present the martyr as a unifying figure attractive to a broad Protestant coalition.